Особенности маточной перистальтики у женщин с гиперпластическими процессами матки = Peculiarities of uterine vermicular movement in the women with hyperplasic processes - Gladchuk, I. Z.; Garbuzenko, N. D. (Journal of Education, Health and Sport, 2016)
Gladchuk I. Z., Garbuzenko N. D. Особенности маточной перистальтики у женщин с гиперпластическими процессами матки = Peculiarities of uterine vermicular movement in the women with hyperplasic processes Journal of Education, Health and Sport. 2016;6(10):578-585. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.179338 http://ojs.ukw.edu.pl/index.php/johs/article/view/4022 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.10.2016. Особенности маточной перистальтики у женщин с гиперпластическими процессами матки И. З. Гладчук, Н. Д. Гарбузенко Одесский национальный медицинский университет PECULIARITIES OF UTERINE VERMICULAR MOVEMENT IN THE WOMEN WITH HYPERPLASIC PROCESSES I. Z. Gladchuk, N. D. Garbuzenko Odessa National Medical University, Ukraine klepa-si@i.ua Summary Background. At the present time the role of uterine pump in physiology of impregnation is recognized as important. Its main diagnostic methods are ultrasonography and hysterosalpingoscintigraphy. Results. The study of uterine vermicular movements has been made in 188 afetal women with hyperplastic processes of uterine. Significant increase of disperistaltic waves frequency has been revealed in adenomiosis patients (р<0,001). D-waves have been revealed in all patients older than 39 y.o. There was a significant decrease of A and B waves in the patients with adenomiosis and uterine myoma (p<0,02). Disperistaltic waves are met significantly often (р<0,05) in the patients with adenomiosis and infertility of more than 5 years. Conclusions. The patients with adenomiosis and disturbances of uterine peristaltic aged 30-35 y.o. should undergo one of in vitro fertilization procedures, omitting intrauterine insemination. Кeywords: adenomiosis, uterine myoma, infertility, uterine vermicular movement.